Persepsi Peserta BPJS Kesehatan Terhadap Pelayanan Puskesmas Kotanopan Kabupaten Mandailing Natal - Seri Wahyuni Lubis (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2023)
The social welfare of the community is very basic and is a benchmark for seeing the progress of a country. One aspect of social welfare that is a problem in Indonesia is health problems. To overcome this, the government established the National Health Insurance (JKN) with the BPJS Kesehatan program. The purpose of this study was to determine the perceptions of health BPJS participants towards services at the Kotanopan Health Center. This type of research uses a qualitative descriptive approach with data analysis of data reduction), data presentation and drawing conclusions. Informants in this study consisted of 7 people. The results of the study show that the perceptions of BPJS health participants regarding the security of patient data are good and health facilities are complete, but for comfort, punctuality, courtesy and friendliness and fairness during the service is still lacking. It is hoped that the Puskesmas will improve the quality of service to patients, especially patient using BPJS at the Puskesmas